Effectiveness of Avocado Seed Extract on the Detergent Production Process - Nolalita, Aureliya Helmaleni; Karyadi, Nabila Putri; Santoso, Shafira Ardaneswari; Paramita, Vita (Vocational College of Universitas Diponegoro, 2024)
This study aims to determine the effectiveness of avocado seed oil as a substitute for SLS which can be used to make environmentally friendly detergents. The method used in this research is mixing. The results obtained in this study are in the density test samples that meet the requirements are sample 1, sample 2, sample 5, and sample 6. In the viscosity test, high viscosity results were shown in sample 6. In the overall results of the pH test, the sample obtained a pH of 11 which did not meet SNI standards. If the pH of a detergent is more than 8-10 it will risk causing irritation to the skin and environmental pollution. In the saponin test, avocado seed extract contains saponin compounds because saponin compounds are known to form foam due to the combination of constituent compound structures. In the foam stability test, the foam produced must last around 60-70% of the initial volume and in the observation there are 4 samples that meet these requirements, namely sample 1, sample 3, sample 6, and sample 7 respectively 72%, 81%, 72%, and 81%. It can be concluded that sample 6 is better than the other samples